Effect of upgaze on lower eyelid position in Korean patients with congenital ptosis. Issue 3 (March 2017) - Teo, Livia; Lee, Sang Yeul; Kim, Chang Yeom
Summary: Purpose: The purpose of this study was to demonstrate accompanying clinical features besides lid droop in congenital ptosis and to determine the effect of upgaze on lower eyelid position in patients with congenital ptosis. Methods: Pediatric patients with congenital ptosis who visited our clinic over a 1-month period in 2014 were recruited for this study. Clinical photographs and measurements were taken prospectively in primary gaze and upgaze. Measurements taken from photographs and clinical records include inferior scleral show (ISS), vertical lower lid height (LL), and canthal tilt angle (CTA). Results: There were 35 patients with congenital ptosis. There was more ISS in unilateral ptosis eyes than in the normal side in both primary gaze (p < 0.05) and upgaze (p < 0.01), with corresponding increase in ISS in upgaze (p < 0.05). There was also more ISS in unilateral ptosis eyes than in bilateral ptosis eyes in primary gaze (p < 0.05) and upgaze (p < 0.01), with accompanying increase in ISS in upgaze (p < 0.01). There was less elevation of the lower lid in unilateral ptosis eyes (0.5 ± 0.7 mm) than in the contralateral normal eyes (0.8 ± 0.7 mm) in upgaze, but this was not statistically significant (p = 0.07). CTA was lower in ptosis eyes than in normal eyes in primary gaze and upgaze (p < 0.01 and p < 0.05, respectively). Conclusion: ISS was larger in ptosis eyes and upgaze appears to increase ISS. Canthal tilt is lower in congenital ptosis eyes than in normal eyes in primary gaze and upgaze.